ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DITINJAU DARI SELF-EFFICACY SELAMA MASA PANDEMI COVID-19 - Banowati, Azzeinafitri; Siswanto, Rizki Dwi (Jurnal Penelitian dan Pembelajaran Matematika, 2023)
This study aims to analyze and describe students’ mathematical understanding abilities in terms of self-efficacy during the Covid-19 pandemic. Methodology in this research used descriptive qualitative. Purposive sampling technique was used to take 6 samples, 1 sample with high self-efficacy male gender, 1 sample with high self-efficacy female gender, 1 sample with moderate self-efficacy male gender, 1 sample with moderate self-efficacy female gender, 1 sample with low self-efficacy male gender, 1 sample with low self-efficacy female gender. Instrument of this study were a questionnaire, a test of mathematical understanding ability and an interview guide. Data analysis technique in this research are data reduction, data display, and conclusion. Test the validity of the data in this study using data triangulation techniques to compare the results of mathematical understanding ability test and the result of the interview. Conclusion of this study are subjects with high self-efficacy of female gender (S2) are better than subjects with high self-efficacy of male gender (S1) in restating a concept both verbally and in writing and classifying objects according to certain characteristics. Subjects with moderate self-efficacy of male gender (S3) were better than subjects with moderate self-efficacy of female gender (S4) in presenting concepts in various forms of mathematical representation and explaining the relationship between one concept and another. Subjects with low self-efficacy of male gender (S5) were better than subjects with low self-efficacy of female gender (S6) in classifying objects according to certain characteristics.